Evolutionary game and stability analysis of elderly care service quality supervision from the perspective of government governance - Wang, Qiangxiang; Liu, June; Zheng, Yue (Frontiers in Public Health, 2023)
Objective The performance of government functions is an important guarantee for the standardized operation of the elderly service market. The objective of this study is to explore the optimal path for the government to govern the elderly care service market. Methods The tripartite evolutionary game model is proposed in the paper, which composed of local governments, private elderly care institutions and the public. Furthermore, three mechanisms, i.e. dynamic penalty and static subsidy, static penalty and dynamic subsidy, dynamic penalty and dynamic subsidy, are designed. Under these different mechanisms, the stability of each subject’s strategy choice is analyzed by using system dynamics simulation. Results The introduction of dynamic mechanisms can compensate for the inability of static mechanisms to bring the system to a steady state. The dynamic penalty and dynamic subsidy mechanism allows the system to evolve to the desired point of stability. The self-discipline behavior of private elderly care institutions is positively correlated with penalties and reputation gains-losses, negatively correlated with subsidies, and not correlated with supervision rewards. Excessive subsidies will promote the collusion of private elderly institutions. Conclusion Only when the local government adopts the dynamic penalty and dynamic subsidy mechanism will private elderly care institutions choose to operate in a fully self-disciplined manner. Reasonable adjustments of penalties, reputation gains-losses and subsidies can not only further optimize the dynamic penalty and dynamic subsidy mechanism, but also help to achieve diversified regulatory objectives of the government. This study would provide a reference for local governments seeking to develop effective regulatory policies for the elderly service market.